DECONSTRUCTION OF LINGUISTICS IMPERIALISM IN INDONESIA’S SCHOOL: OVERSEEING THE ELT TEXTBOOKS - Anggraini Saiful, Sri Hastuti Novila; MAHURNI; Aini, Nurul (Cordova Journal language and culture studies, 2025)
For over a decade, the unceasing dissemination of English as a global language, consciously or not, has influenced the concepts of the ELT across the world. Some countries persist in the adaptation of the concepts of EFL or ESL in their practical ELT contexts wherein the cultures of the inner-circle countries, like the US and the British, are still dominant in their teaching materials. Others; however, prefer to alternate the ELT concepts to either EIL or ELF in their own teaching contexts in which the cultural contexts in the teaching materials are the integrations of the cultures of the inner-circles, the outer-circle, and the expanded countries or the international cultures along with their own local cultures. This paper aimed to overview the deconstruction of the formulation concepts of the cultural dominance in the ELT textbook in the context of Indonesia’s high schools. This review addresses the dichotomies of the concepts of EFL/ESL, EILand ELF along with the cultural dominances embedded on the conceptual terms. This study is literature -based research when collecting data through extensive and critical reading and analysis of existing academic works related to ELT, cultural representation, and linguistic imperialism. Thisstudy draws on existing academic works to explore how the hegemony of English is embedded in English textbooks. The result of this study shows that the linguistics imperialism continues shaping the materials and sources of ELT textbooksin Indonesia. The content and structed of Indonesian ELT textbooks highlight the cultural values and perspective of inner-circle countries. Although EFL concept is still dominated in Indonesian context, there is a growing awareness of the need to shift towards more inclusive curriculum when local content and perspective more embedded. Further, this research elucidates critical reflections on an ideology, economy, and politics of language the linguistics Imperialism, as well as possible recommendation to what possible, applicable concepts should be adjusted to the Indonesia’s ELT textbook.